O Fenômeno da Desinformação no WhatsApp, Telegram e Outras Plataformas de Mensagens Instantâneas: Uma Revisão Sistemática da Literatura - Olivetti, João Francisco Hecksher; Bomfim, Ana Flávia; Oliveira, Marcos; Marques, Helom Felipe; Avelar, Juan; Reis, Julio C. S.; Melo, Philipe (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2025)
This literature review examines the current state of research on misinformation within Instant Messaging Platforms (IMPs) such as WhatsApp, Telegram and WeChat. By conducting comprehensive searches across multiple repositories, we identified 110 relevant studies published between 2018 and 2025, covering more than 20 countries and 7 distinct messaging platforms. These works were systematically analyzed to: (i) map internal and external factors of IMPs that facilitate the creation and spread of misinformation; (ii) identify its main impacts and negative consequences reported to our society; and (iii) examine strategies proposed or implemented to mitigate and to combat misinformation within this environment. Our findings reveal recurrent themes across studies employing diverse methodologies, indicating a growing convergence in this still-fragmented research field, while also exposing points of disagreement. The analysis highlights how specific architectural features make IMPs uniquely susceptible to misinformation. Unlike mainstream social networks, their information flow is governed directly by user interactions rather than feed algorithms. In this context, end-to-end encryption, high virality, and limited moderation or fact-checking emerge as internal components that sustain the misinformation ecosystem. Externally, factors such as low digital literacy, social polarization, and political bias further reinforce the problem. Notably, some elements such as distrust in institutions and political polarization are reported both as causes and as consequences of misinformation, suggesting a potential self-reinforcing cycle. Crucially, our review shed light on a paradoxical communication architecture in IMPs, where encrypted and seemingly personal messages coexist seamlessly with large-scale, viral dissemination. This duality blurs the distinction for users between intimate communication and mass circulation, making it harder to assess the origin and credibility of information.